Primerjava učinkovitosti analgezije s PCEA, PCA ter 5-odstotnim lidokainskim obližem pri laparoskopskih resekcijah črevesa - Spindler-Vesel, Alenka (Endoskopska revija, 2011)
Background. Postoperative pain in patients undergoing laparoscopic colorectal surgery can be relieved by thoracic epidural analgesia (TEA). Since the laparoscopic procedure is less invasive, it is judicious to use a less invasive analgesia, such as intravenous opioids. Consumption of opioids can bereduced by applying a lidocaine patch to the wound site. The aim of this study was to compare the efficiency of postoperative pain relief provided withTEA and with infusion of piritramide (patient controlled analgesia, PCA), alone or combined with a lidocaine patch 5% applied to the wound site. Methods. We studied prospectively 39 patients older than 18 years, ASA (American Society of Anesthesiologists, ASA) I-III, who were scheduled for elective colorectal surgery. The patients were randomly divided into three groups, as follows: group 1 (N=13) received patient controlled epidural analgesia (PCEA), group 2 (N=13) received a continuous infusion of piritramide(PCA), and group 3 (N=13) had PCA and a lidocaine patch 5% applied to the wound site. Postoperative analgesia was recorded every six hours, and postoperative pain scores were measured on a visual analogue scale (VAS). Piritramide consumption on the day of surgery and during the first two postoperative days was recorded both in the recovery room and on the intensivecare ward. Results. In the period studied, no statistically significant differences in demographic data and VAS were found between the groups. On the first postoperative day, patients in group 3 needed less piritramide than those in group 2 (p = 0.05). Conclusions. A lidocaine patch 5% applied to the wound site reduces piritramide consumption for postoperativepain relief in patients undergoing laparoscopic colorectal surgery, and decreases the risk of complications associated with strong opioids.
Keywords: analgezija; bolečina; kolorektalne novotvorbe; laparoskopija